Different performance of three point-of-care SARS-CoV-2 antigen detection devices in symptomatic patients and close asymptomatic contacts: a real-life study. (June 2022) - Escribano, Pilar; Sánchez-Pulido, Ana-Erika; González-Leiva, José; Valero-López, Iván; Catalán, Pilar; Muñoz, Patricia; Guinea, Jesús; ,; Adán, Iván; Adán, Javier; Alcalá, Luis; Alonso, Roberto; et al.
Abstract: Objectives: PCR on nasopharyngeal exudates, the cornerstone of the detection of SARS-CoV-2, is time-consuming and commonly unavailable at primary health care centres. Detection of viral nucleocapsid antigens using lateral flow point-of-care tests is helpful for the early triage of patients who attend health care facilities. Methods: This was a prospective study carried out in clinically suspected cases and close asymptomatic contacts who attended a primary care centre (Madrid, Spain) for SARS-CoV-2 detection. Patients were divided into three 300-patient cohorts ( n = 200 symptomatic cases and n = 100 close asymptomatic contacts per cohort). Three antigen detection tests (SGTI-Flex COVID-19 Ag, Panbio COVID-19 Ag Rapid Test Device, and GSD NovaGen SARS-CoV-2 Ag Rapid Test) were used and compared. Paired nasopharyngeal exudates were obtained, one swab for PCR and the other for antigen detection. Each antigen detection test was evaluated on one cohort. Results: All tests showed invariably 100% specificity. Sensitivity was 68.9% (95% CI: 55.7–80; SGTI-Flex), 71.1% (95% CI: 55.6–83.6; Panbio), and 84.6% (95% CI: 72–93.1; NovaGen) in clinically suspected patients and 84.6% (95% CI: 54.5–98.1), 33.3% (95% CI: 11.8–61.6), and 55.6% (95% CI: 30.7–78.4) in close asymptomatic contacts, respectively. Sensitivity was systematically higher in samples yielding positive PCR results with Ct ≤ 20. Discussion: We found considerable test-to-test antigen detection variations among patients with clinical suspicion of COVID-19 and close asymptomatic contacts. Negative antigen results, regardless of the test used, should be confirmed by PCR. Graphical abstract: Image 1